Perlindungan Hukum bagi Konsumen terhadap Kerugian dalam Layanan Penggunaan Paket Internet provider - Nurin Fitriana Ulfa; I Nyoman Putu Budiartha; Desak Gde Dwi Arini (Fakultas Hukum, Universitas Warmadewa, 2020)
Legal protection for consumers is a process of protection provided to consumers in their efforts to obtain the desired goods and/or services and the possibility of a loss in using them, the law applies to protect consumers. This study aims to find out the legal protection for consumers of providers against losses in the use of internet data packages that have used up but have not received notification and responsibility of the provider for the loss of consumers of internet data package users. The method used in this study is empirical legal research using a statutory, conceptual and sociological approach. Primary and secondary data is data used in this study. Then this study was analyzed qualitatively. Based on the analysis, the results of this study indicate that the legal protection for consumers against losses in services using the internet provider package is the process of resolving disputes with accountability by Telkomsel. Liability as an effort to protect consumers from the provider to consumers that results in consumer losses in the form of credit cuts has not been fully implemented, because not all provider problems will be given compensation in any form.